2021
DOI: 10.1038/s41427-021-00344-6
|View full text |Cite
|
Sign up to set email alerts
|

Field-like spin–orbit torque induced by bulk Rashba channels in GeTe/NiFe bilayers

Abstract: Most studies of the Rashba effect have focused on interfacial Rashba spin–orbit coupling. Recently, bulk Rashba materials have attracted considerable interest owing to their potential to enhance the Rashba spin–orbit torque. By employing a bulk Rashba material, GeTe, as a spin–orbit channel in GeTe/NiFe bilayers, a large field-like spin–orbit torque up to 15.8 mT/(107 A cm−2) is measured. This value is one of the largest reported field-like torques and is attributed to the interfacial spin–orbit coupling being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We speculate that the TI channel is an extreme case of a Rashba channel; it is therefore reasonable that the field-like torque is much larger than the damping-like torque. Indeed, the previous studies on strong Rashba channels have demonstrated that field-like torques is stronger than damping-like torque in an InAs quantum well and GeTe bulk Rashba channels …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the TI channel is an extreme case of a Rashba channel; it is therefore reasonable that the field-like torque is much larger than the damping-like torque. Indeed, the previous studies on strong Rashba channels have demonstrated that field-like torques is stronger than damping-like torque in an InAs quantum well and GeTe bulk Rashba channels …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the previous studies on strong Rashba channels have demonstrated that field-like torques is stronger than dampinglike torque in an InAs quantum well 29 and GeTe bulk Rashba channels. 30 To investigate the gate-controlled spin−orbit field, we modulated the Fermi level of TI using an applied gate voltage to the spin−orbit channel while measuring the secondharmonic signals. Figure 4a shows the gate dependence of the effective spin−orbit field from the harmonic measurement for various gate voltages (Supporting Information S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the deterministic writing is realized by modulating the λ FL /λ DL ratio. Typically, there are some representative methodologies to modulate the ratio of λ FL /λ DL ; for instance, by means of either the bulk Rashba channels enhancement or the interfacial spin accumulation, it is amenable to enhance the FL torque and boost the ratio of λ FL /λ DL up to 4 [54]. By annealing at the proper temperature, the ratio of λ FL /λ DL can be greatly enhanced due to the improvement of interfacial spin transparency [55].…”
Section: Proposed Device Structure and Parameters Optimizationmentioning
confidence: 99%